2009
DOI: 10.1590/s0103-64402009000400008
|View full text |Cite
|
Sign up to set email alerts
|

Validity of staining and marginal ditching as criteria for diagnosis of secondary caries around occlusal amalgam restorations: an in vitro study

Abstract: This study determined the validity of marginal ditching and staining as criteria for the diagnosis of secondary caries around amalgam restorations. One hundred and twenty-four Class I amalgam restorations on extracted human teeth were submitted to standardized clinical examinations. A calibrated examiner recorded the presence of ditching in the tooth/restoration interface, the occurrence of bluish-grey staining on the occlusal surface, and their relationship with the presence and severity of secondary carious … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2010
2010
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 15 publications
2
17
0
Order By: Relevance
“…Nevertheless, the lack of standardized diagnostic criteria for marginal failure could cause over‐registration of secondary caries . Crevices and ditched margins in which the explorer sticks, and marginal colour changes, could be wrongly diagnosed as secondary caries .…”
Section: Discussionsupporting
confidence: 92%
“…Nevertheless, the lack of standardized diagnostic criteria for marginal failure could cause over‐registration of secondary caries . Crevices and ditched margins in which the explorer sticks, and marginal colour changes, could be wrongly diagnosed as secondary caries .…”
Section: Discussionsupporting
confidence: 92%
“…The validity of staining and marginal ditching as criteria for the diagnosis of secondary caries around occlusal amalgam restorations is also questionable and not accepted today. 22,30,31,37 Conversely, the size of marginal gaps has been correlated to the presence of carious lesions if the gap is wider than 0.4 mm, which is difficult to measure clinically. 22,31 The determination of the patient´s caries risk level is the typically used instrument for predicting caries performance for patients, and in the present study this evaluation was only made at baseline, at this time.…”
Section: Discussionmentioning
confidence: 99%
“…22,30,31,37 Conversely, the size of marginal gaps has been correlated to the presence of carious lesions if the gap is wider than 0.4 mm, which is difficult to measure clinically. 22,31 The determination of the patient´s caries risk level is the typically used instrument for predicting caries performance for patients, and in the present study this evaluation was only made at baseline, at this time. Caries risk, considered as a dynamic index, may change over time, but the caries risk was not evaluated each year, and it would have been important to know and to explain the results of the untreated group in secondary caries parameter.In cariogram evaluation, clinical judge parameter was included, and it did not showed major influence over final score, because patients live in a high caries risk area, according to WHO, this fact probably reduces the bias of the clinical judge over final score.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The diagnosis of secondary caries is a subjective topic, which can lead to an inappropriate indication of restorative treatment. This diagnosis is based on external indicators such as restoration defects, discoloration at the margins of the restorative material, microbial accumulation, and tooth-restoration gaps (KIDD; JOYSTON-BECHAL; BEIGHTON, 1995;BEIGHTON, 1996;FONTANA;GONZÁLES-CABEZAS, 2000;MAGALHÃES et al, 2009;LAI;LI, 2012). However, a number of studies have shown that external clinical indication is not efficacious in the diagnosis of secondary caries (GOLDBERG et al, 1981;O'HARA, 1990;BEIGHTON, 1994;BEIGHTON, 1995;PENNING, 1995;PIMENTA;NAVARRO;CONSOLARO, 1995;BEIGHTON, 1996; RUDOLPHY; VAN LOVEREN; VAN AMERONGEN, 1996).…”
Section: Introductionmentioning
confidence: 99%